If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5a-4(a-8)=3+2a
We simplify the equation to the form, which is simple to understand
5a-4(a-8)=3+2a
Reorder the terms in parentheses
5a+(-4a+32)=3+2a
Remove unnecessary parentheses
+5a-4a+32=+3+2a
We move all terms containing a to the left and all other terms to the right.
+5a-4a-2a=+3-32
We simplify left and right side of the equation.
-1a=-29
We divide both sides of the equation by -1 to get a.
a=29
| t*g^2*x-(1)=0 | | -6.5x^2+1.6+24=0 | | (-7)-(-2)= | | 4l^4m^5n^6/5mn= | | y=22-9 | | 4g^2= | | 13-2j=-29 | | 8×2/3 | | 4p+34.8=68 | | 9n^6-16p^2= | | 33-y=2 | | 6(1k-7)-2=5 | | 7+(-7)= | | 4x^2+7=4x+6 | | y=-16x^2+60x+6 | | y+3=0fory | | 5x^2-10=x^2+71 | | 3t+5+3t-5t=6+5 | | 16t^2+40tx+25x^2= | | x/3=-2-(-6) | | 6(-5/7) | | 20m-35= | | (4x-20)=(2x+10) | | x-4(99-11x)-1.584=0 | | -3(3y+1)-13=-6(y+5)+3y | | (-6)-1= | | (2x^2)/(.5-x^2) | | 3x-2x-9=2 | | a^2+25+10a=0 | | (-1)+2= | | 3x-2x-9=3 | | y=ln(5-8x) |